The Breaths of al-Dāstānī and the Heirs of al-Bisṭāmī: Formation of Intoxicated Sufism in Persia - Kars, Aydogan 19XX- (Journal of Sufi studies, 2025)
This paper analyzes the legacy of intoxicated Sufism, with a focus on the Sufi master Abū ʿAbd Allāh Muḥammad Ibn ʿAlī al-Dāstānī (d. 417/1026). Al-Dāstānī is depicted as a prominent figure among the early followers of the ecstatic mystic Bāyazīd Ṭayfūr al-Bisṭāmī (d. 234/848) in Bistam, known as the Ṭayfūriyya. Little is known, however, about the formalization of leadership and spiritual authority among the early followers of Bāyazīd, and about the connections between these early groups and the later Sufi movements, such as the Bisṭāmiyya that emerged in fourteenth-century Levant. In this paper, I argue that al-Dāstānī played a major role in the formalization of leadership among the heirs of Bāyazīd, through examining previously untapped sources that shed light on this figure and introducing an understudied Arabic treatise that narrates his teachings.